The Broad Reach of Multivariable Thinking - Kuhn, Deanna; Modrek, Anahid (Informal Logic)

(untitled) (Informal Logic, 2023)
Simple explanations are very often inadequate and can encourage faulty inferences. We examined college students’ explanations regarding illegal immigration to determine the prevalence of single-factor explanations. The form of students’ explanations was predicted by their responses on a simple three-item forced-choice multivariable causal reasoning task in which they selected the strongest evidence against a causal claim. In a further qualitative investigation of explanations by a sample of community adults, we identified positive features among those who scored high on this multivariable causal reasoning task. We consider limitations of single-factor reasoning and means of encouraging more comprehensive explanations to support claims.